2008
DOI: 10.1111/j.1467-8276.2008.01176.x
|View full text |Cite
|
Sign up to set email alerts
|

Brand Inertia in U.S. Household Cheese Consumption

Abstract: To analyze U.S. consumers' brand choices for cheese purchases, we derive a set of discrete-choice models from dynamic utility maximization. ACNielsen Homescan Survey data on U.S. households is used to estimate a dynamic probit model for each of the top brands for cheddar, shredded, and sliced cheese in four U.S. regions. We find that households have strong brand inertia, a result robust across alternative specifications. Predicted probabilities confirm greater inertia in the top brands and consumers are more l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…The educational attainment of the head of the household was expected to be negatively correlated to the probability of purchase of private label product because previous studies (Arnade et al, 2008) found that greater levels of education positively affected the choice of the purchase of top brand cheese products. The opposite was revealed in our analysis.…”
Section: Interpretation Of Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The educational attainment of the head of the household was expected to be negatively correlated to the probability of purchase of private label product because previous studies (Arnade et al, 2008) found that greater levels of education positively affected the choice of the purchase of top brand cheese products. The opposite was revealed in our analysis.…”
Section: Interpretation Of Resultsmentioning
confidence: 98%
“…According to Arnade et al (2008), a greater level of education positively affected the purchase of top brand cheese products. The educational attainment of the head of the household then is expected to be negatively correlated to the probability of purchasing a private label product.…”
Section: Choice Of Explanatory Variables and Expected Signsmentioning
confidence: 97%
See 3 more Smart Citations